Decoding Gene Networks Modules That Explain the Recovery of Hymenoglossum cruentum Cav. After Extreme Desiccation - Ostria-Gallardo, Enrique; Larama, Giovanni; Berríos, Graciela; Fallard, Ana; Gutiérrez-Moraga, Ana; Ensminger, Ingo; Manque, Patricio; Bascuñán-Godoy, Luisa; Bravo, León A. (Frontiers in Plant Science, 2020)
Hymenoglossum cruentum (Hymenophyllaceae) is a poikilohydric, homoiochlorophyllous desiccation-tolerant (DT) epiphyte fern. It can undergo fast and frequent dehydration-rehydration cycles. This fern is highly abundant at high-humidity/low-light microenvironments within the canopy, although rapid changes in humidity and light intensity are frequent. The objective of this study is to study the transcriptome of H. cruentum to better understand the genetic dynamics behind its desiccation tolerance mechanism. H. cruentum plants were subjected to a seven days long desiccation-rehydration process and then used to identify the expression of key genes associated to its capacity to dehydrate and rehydrate. The relative water content (RWC) and maximum quantum efficiency (Fv/Fm) of H. cruentum fronds decayed to 6% and 0.04, respectively, at the end of the desiccation stage. After re-watering, the fern showed a rapid recovery of RWC and Fv/Fm (ca. 73% and 0.8, respectively). Based on clustering and network analysis on transcriptome data, our results reveal key genes orchestrating a preventive state at full hydrated; strong balance between avoiding cell death and defense when dehydrated, and detoxifying pathways and stabilization of photosystems during rehydration. Here we provide novel insights into the genetic dynamics behind the desiccation tolerance mechanism of H. cruentum.